2019
DOI: 10.3847/2041-8213/ab2a15
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Dominant Acceleration Mechanism during Relativistic Magnetic Reconnection in Large-scale Systems

Abstract: While a growing body of research indicates that relativistic magnetic reconnection is a prodigious source of particle acceleration in high-energy astrophysical systems, the dominant acceleration mechanism remains controversial. Using a combination of fully kinetic simulations and theoretical analysis, we demonstrate that Fermi-type acceleration within the large-scale motional electric fields dominates over direct acceleration from non-ideal electric fields within small-scale diffusion regions. This result has … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
99
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(112 citation statements)
references
References 53 publications
7
99
5
1
Order By: Relevance
“…More recently, Brunetti and Lazarian [37] proposed a mechanism that operates in large-scale super-Alfvénic solenoidal turbulence in the ICM, where particles are reaccelerated stochastically diffusing across regions of magnetic reconnection and dynamo [see 38,39, for application to gamma-ray bursts and Pulsar wind nebulae]. On much smaller scales, situations involving first order and second order Fermi-like acceleration are also observed in simulations of reconnection regions [e.g., [40][41][42][43]. In the case of prevalence of solenoidal component and strongly super-Alfvénic turbulence,…”
mentioning
confidence: 99%
“…More recently, Brunetti and Lazarian [37] proposed a mechanism that operates in large-scale super-Alfvénic solenoidal turbulence in the ICM, where particles are reaccelerated stochastically diffusing across regions of magnetic reconnection and dynamo [see 38,39, for application to gamma-ray bursts and Pulsar wind nebulae]. On much smaller scales, situations involving first order and second order Fermi-like acceleration are also observed in simulations of reconnection regions [e.g., [40][41][42][43]. In the case of prevalence of solenoidal component and strongly super-Alfvénic turbulence,…”
mentioning
confidence: 99%
“…Recent kinetic simulations of magnetic reconnection in the relativistic regime have shown the formation of power-law energy spectra (e.g. Guo et al 2014Guo et al , 2015Guo et al , 2019Sironi & Spitkovsky 2014;Werner et al 2016). However, obtaining power-law distributions in the nonrelativistic regime relevant to solar flares is considerably more difficult.…”
mentioning
confidence: 99%
“…Sironi and Spitkovsky [26] have suggested that the power-law forms as the particles interact with the X-points (diffusion regions with weak magnetic field |E| > |B|) through direct acceleration. In contrast, analyses by Guo et al [25,27,29] show that the power-law distributions are produced by Fermi-like processes and continuous injection from the reconnection inflow. In the case of the shockdriven reconnection at the termination shocks of highly relativistic striped pulsar winds, Sironi and Spitkovsky [20] have proposed that high-energy particles are mainly accelerated at the electric fields at the X-points.…”
Section: Introductionmentioning
confidence: 86%
“…For such local frames, we can decompose the electric fields based on Lorentz transformation, with detailed derivations given in the Appendix C 1 and C 2. The ways we decompose the electric fields are a generalization for the non-relativistic case used extensively in previous studies [25,27,29,37]. This generalization is critical in this work because the motion of the bulk flow in our simulations can be highly relativistic.…”
Section: Particle Acceleration Mechanismmentioning
confidence: 99%
See 1 more Smart Citation